Hysteresis Effects on Unemployment Rates: A Comparative Study of the Baltic States Before and After EU Accession - Köse, Tuna (Organizations and Markets in Emerging Economies, 2025)
This study examines the hysteresis effects on unemployment rates in the Baltic countries using the RALS-LM unit root test method, based on monthly data from February 2000 to August 2024. It assesses the persistence of unemployment by gender, focusing on both female and male unemployment rates. Additionally, the study provides a detailed evaluation of the hysteresis effects observed on unemployment rates before and after the Baltic countries’ accession to the European Union (EU). The findings show that the unemployment rates in these countries are highly sensitive to long-term structural changes. Structural breaks occurred mainly between 2001 and 2003 before EU accession, while the 2008–2009 Global Financial Crisis and the European Debt Crisis shifted these breaks to the 2007–2010 period. Significant structural changes in total unemployment were observed in Estonia and Lithuania after their EU accession. The results indicate hysteresis effects in Estonia and Latvia, whereas Lithuania shows varying patterns of unemployment persistence. This study highlights the importance of understanding the long-term effects of structural changes and external shocks on labor market dynamics in the Baltic countries.
Keywords: unemployment; hysteresis; Baltic countries; RALS-LM